2008
DOI: 10.1007/s00232-008-9132-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Topiramate Modulates Brain Microsomal Oxidative Stress Values, Ca2+-ATPase Activity, and EEG Records in Pentylentetrazol-Induced Seizures in Rats

Abstract: It has been suggested that oxidative stress products play an important role in the etiology of epilepsy. We investigated the effects of selenium (Se) administration on topiramate (TPM)- and pentylentetrazol (PTZ)-induced brain toxicity in rats. Forty male Wistar rats were divided into five equal groups. The first and second groups were used as the control and PTZ groups, respectively. TPM, 50 mg, and Se, 0.3 mg, were administered to rats constituting the third and fourth groups, respectively, for 7 days. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 46 publications
6
56
0
1
Order By: Relevance
“…ROS production in an uncontrolled fashion causes important damage to a wide range of biological molecules, such as DNA, lipids, proteins, carbohydrates, or any nearby molecule causing a cascade of chain reactions resulting in neuronal damage and epilepsy (Nazıroğlu, 2009). Oxidative stress has been implicated in the genesis and progression of epileptic seizures (Nazıroğlu et al, 2008;Kutluhan et al, 2009;Demirci et al, 2013). The ROS in the neurons of epileptic animals and humans are controlled by antioxidants, including melatonin (Table 2).…”
Section: Melatonin and Trp Channelsmentioning
confidence: 99%
“…ROS production in an uncontrolled fashion causes important damage to a wide range of biological molecules, such as DNA, lipids, proteins, carbohydrates, or any nearby molecule causing a cascade of chain reactions resulting in neuronal damage and epilepsy (Nazıroğlu, 2009). Oxidative stress has been implicated in the genesis and progression of epileptic seizures (Nazıroğlu et al, 2008;Kutluhan et al, 2009;Demirci et al, 2013). The ROS in the neurons of epileptic animals and humans are controlled by antioxidants, including melatonin (Table 2).…”
Section: Melatonin and Trp Channelsmentioning
confidence: 99%
“…Furthermore, erythrocyte GR and plasma ascorbate and vitamin A concentrations were lower [79]. In the majority of these studies also increased markers of lipid peroxidation were noted [75,[77][78][79][80][81][82].…”
Section: Influence Of Aeds On Antioxidants and Markers Of Oxidative Smentioning
confidence: 91%
“…[31] A decrease in NO amounts is followed by a corresponding decrease in the GABA levels via an increase in the GABA transaminase activity. [32] Naziroglu et al [21] showed no differences in the NO levels in the brain cortex of rats when seizures were induced with PTZ. Ilhan et al [15,23] in two studies documented an increase in NO levels in the brain cortex of rats that had seizures induced with PTZ.…”
Section: Mda Determinationmentioning
confidence: 98%
“…This result is in accordance with the literature findings. [9,11,14,15,21,22] However, the results concerning antioxidant enzyme activities are somewhat conflicting. Discrepancies can be explained by methodological differences, or elevated enzyme activities may be reduced because of oxidative stress.…”
Section: Mda Determinationmentioning
confidence: 99%
See 1 more Smart Citation